High Lithium-Ion-Conducting NASICON-Type Li1+xAlxGeyTi2−x−y(PO4)3 Solid Electrolyte - Xuefu, Shang; Nemori, Hiroyoshi; Mitsuoka, Shigehi; Xu, Peng; Matsui, Masaki; Takeda, Yasuo; Yamamoto, Osamu; Imanishi, Nobuyuki (Frontiers in Energy Research, 2016)
A water-stable solid electrolyte is a key material without which aqueous lithium-air batteries could not be operated. In this study, we have examined the electrical conductivity and mechanical properties of a water-stable lithium ion conducting solid electrolyte, Li1+xAlxGeyTi2-x-y(PO4)3 with the NASICON-type structure, as a function of the Al and Ge content. Li1+xAlxGeyTi2-x-y(PO4)3 was synthesized by the conventional solid-state reaction method. The highest lithium-ion conductivity of 1.0×10-3 S cm-1 at 25 °C and the highest three-point bending strength of 90 N mm-2 at room temperature were observed for a pellet of Li1.45Al0.45Ge0.2Ti1.35(PO4)3 sintered at 900 °C.